2009
DOI: 10.1111/j.1463-1318.2009.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

The indication and surgical results of local excision following radiotherapy for low rectal cancer

Abstract: Local excision followed adjuvant radiotherapy is an alternative and feasible technique for small T1 rectal cancer in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…CT scans were used to detect metastatic disease in 17 out of these 20 studies. Local staging in the form of endoanal ultrasound alone was performed in eight studies , MRI alone in four studies and combined endoanal ultrasound and MRI in four studies . Endoscopic evaluation was reported by nine studies .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CT scans were used to detect metastatic disease in 17 out of these 20 studies. Local staging in the form of endoanal ultrasound alone was performed in eight studies , MRI alone in four studies and combined endoanal ultrasound and MRI in four studies . Endoscopic evaluation was reported by nine studies .…”
Section: Resultsmentioning
confidence: 99%
“…Radiotherapy dosing ranged from 15 to 67 Gy. Concomitant use of adjuvant chemotherapy was in the form of fluorouracil (5‐FU) in seven studies , 5‐FU/leucovorin in three studies and capecitabine in two studies . Eight studies reported the interval from local excision to commencement of adjuvant therapy and this was between 2 and 6 weeks postoperatively except for Valentini et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations